Comparative assay of protease enzyme activity in protoscolices (Hydatid cyst) and liver tissues - Anasori, Narges; Farahnak, Ali; Golmohamadi, Taghi; Eshraghian, Mohamadreza; Molaei Rad, Mohamadbagher (Archives of Advances in Biosciences, 2015)
Hydatidosis is a zoonosis disease caused by the larva of Echinococcus granulosus parasite in man and animals. The Proteases enzymes are necessary for nutrition, migration and evasion of immunity of parasite into host. The aim of this study was to determine the protease activity of hydatid cyst protoscolices (PSC), healthy and cystic liver tissues in order to compare of this biomarker for host and parasite in hydatid disease. In this study, PSC were collected from sheep liver tissue infected with hydatid cysts at an abattoir and washed 3 times with PBS buffer. PSC samples were freeze-thawed and sonicated while collected liver tissues were homogenized. Extract solution samples were centrifuged and stored at - 20°C. Protease enzymes activity was measured in the extract solutions of PSC and sheep liver tissue samples (healthy and cystic livers). Samples protein concentrations and protein bands were detected using Bradford and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) methods respectively. To determine significant difference between two groups, statistical t-test was performed. The values of protease enzyme activities in healthy, cystic and PSC were determined 0.0028, 0.0087 and 0.50U/ml/mg respectively. Elevation of protease enzyme activity in cystic liver as compared with healthy was not significant. Statistical T-test showed higher protease enzyme activity for PSC as compared to healthy (p<0.05). SDS-PAGE confirmed 24 kDa and 54 kDa bands for protease enzyme in PSC samples and 24 kDa band in liver samples. Protease enzyme activity and molecular weight as compared to healthy liver tissues could be concerned as a comparative metabolic biomarker for host and parasite in hydatidosis